Determinants of Small Business Tax Compliance Behaviour: Evidence From Zimbabwean Small Businesses - Munyaradzi DUVE; Danie SCHUTTE; Manjit KOUR (Studia Universitatis Babeş-Bolyai Negotia)
Many developing countries have implemented tax regulations for small enterprises and the simplification of tax systems in recent times. Tax compliance attitudes within this sector vary significantly due to the high cost to comply and the technical nature of tax law. Many different factors influence presumptive tax compliance and previous research did not necessarily identify the determinants of this phenomenon. Two hundred and nineteen small business owners/managers participated in the study. The validation of the measurement model and the structural model was performed using the Partial-Least Squares Structural Equation Model. The study evaluated the impact of tax morale, corruption and taxpayer/tax office relationships on presumptive tax compliance in the Zimbabwean context. It was found that corruption significantly influences small business operators’ compliance levels under a presumptive tax system. Significant differences were found in small business owners and managers who differed in their perceptions of their relationships with the tax office. The results of this study would assist tax authorities in understanding small businesses’ perceptions when reviewing the current presumptive tax systems.